Emilia Pardo Umaña: memories of the first colombian female columnist - Flórez Giraldo, Lina Patricia; Pérez, Pablo (Folios, revista de la Facultad de Comunicaciones y Filología, 2012)
Emilia Pardo Umaña (1907-1961) was an important woman in the history of Colombian opinion journalism. For thirty years of professional life, she worked mainly on the field of opinion columnist and was notable for her versatility when choosing different topics that she developed with original arguments. One of her greatest skills was to be consistent with her audience, interpreting and translating their interests into articles that resonated with her readers. As a columnist, she went from criticism to irony in matters ranging from politics to everyday life. As a reporter, she was the first woman in the history of Colombia to actively participate in a newsroom, looking for sources, researching, walking the streets of Bogota. As a chronicler, she dazzled with her narrative style, intimate and intelligent. As a woman, she broke schemes to avoid being typecas in the silent servile position that society gave to women of her time.